Optimizing Smartphone Power Consumption through Dynamic Resolution Scaling - He, Songtao; Liu, Yunxin; Zhou, Hucheng (The 21st Annual International Conference on Mobile Computing and Networking (MobiCom 2015), 2015)
The extremely-high display density of modern smartphones imposes a significant burden on power consumption, yet does not always provide an improved user experience and may even lead to a compromised user experience. As human visually-perceivable ability highly depends on the user-screen distance, a reduced display resolution may still achieve the same user experience when the user-screen distance is large. This provides new power-saving opportunities. In this paper, we present a exible dynamic resolution scaling system for smartphones. The system adopts an ultrasonic-based approach to accurately detect the user-screen distance at low-power cost and makes scaling decisions automatically for maximum user experience and power saving. App developers or users can also adjust the resolution manually as their needs. Our system is able to work on existing commercial smartphones and support legacy apps, without requiring re-building the ROM or any changes of apps. An end-toend dynamic resolution scaling system is implemented on the Galaxy S5 LTE-A and Nexus 6 smartphones, and the correctness and effectiveness are evaluated against 30 games and benchmarks. Experimental results show that all the 30 apps can run successfully with per-frame, real-time dynamic resolution scaling. The energy per frame can be reduced by 30.1% on average and up to 60.5% at most when the resolution is halved, for 15 apps. A user study with 10 users indicates that our system remains good user experience, as none of the 10 users could perceive the resolution changes in the user study.